The Evolution of the Supersoft X-Ray Source WX Cen Dominated by Magnetic Wind - Zang, Lei (2023)
WX Cen is most likely one of the Galactic counterparts of compact binary supersoft X-ray sources as a member of the V Sagittae class, in which mass is transferred from a donor secondary to a massive white dwarf primary via an accretion disk. Based on the photometric observations from the TESS space telescope and AAVSO database, 218 times of light minimum were determined. By collecting all available eclipse timings of WX Cen from the literature together with those newly determined, we constructed an O−C diagram and analyzed the variations in the orbital period of the eclipsing binary. It is confirmed that the orbital period is continuously decreasing and the rate of the change in the orbital period is revised to P = -4.4(4)x10⁻⁷day yr⁻¹ = -0.038(3) s yr⁻¹. The mass of the donor secondary is estimated as Ms ∼ 0.6 Me☉, when the white dwarf mass is MWD ∼ 0.9 M☉ By considering a conservative mass transfer from the secondary to the primary, the orbital period of WX Cen should be increasing, which is opposite to the observed continuous decrease. Therefore, the decrease in the period can be plausibly explained as the result of angular momentum loss (AML) via magnetic wind from the secondary and/or from the accretion disk. The AML causes the donor secondary with a low mass to continually be filling its critical Roche lobe and transferring material to the white dwarf. In this way, the evolution of WX Cen is dominated by the magnetic wind and continuously radiating supersoft X-rays.